2017
DOI: 10.2147/ndt.s144955
|View full text |Cite
|
Sign up to set email alerts
|

Migraine in young females with irritable bowel syndrome: still a challenge

Abstract: Migraine without aura is frequently reported in female patients with irritable bowel syndrome (IBS), but knowledge about the relationship between these two conditions is still lacking. This study was aimed to explore the particularities of migraine without aura in young female patients with IBS in order to establish a possible link between them. From a cohort of young female patients hospitalized with IBS in the Internal Medicine Department, 30 joined this pilot study, and they were assigned into two groups on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…That is, women reported more severe abdominal pain following menopause than before menopause. 32 However, another study demonstrated that there was no significant difference (P > 0.05) in IBS severity score system (IBS-SSS) between pre-and postmenopausal women. 34 However, there are several limitations in the qualities, methods, and numbers of studies evaluating the effect of menstrual cycle, hormone supplementation, and menopausal status on IBS symptoms.…”
Section: Clinical Symptomsmentioning
confidence: 96%
See 1 more Smart Citation
“…That is, women reported more severe abdominal pain following menopause than before menopause. 32 However, another study demonstrated that there was no significant difference (P > 0.05) in IBS severity score system (IBS-SSS) between pre-and postmenopausal women. 34 However, there are several limitations in the qualities, methods, and numbers of studies evaluating the effect of menstrual cycle, hormone supplementation, and menopausal status on IBS symptoms.…”
Section: Clinical Symptomsmentioning
confidence: 96%
“…16 In addition, the prevalences of chronic pain disorders that often overlap with IBS, such as fibromyalgia, chronic fatigue syndrome, chronic pelvic pain, and migraine headache, are higher in women with IBS, suggesting an association between their symptoms and hormonal statuses. 25,27,[29][30][31][32] Women report more frequent and severe IBS symptoms during menstruation such as loose stools, bloating, and worsening of abdominal pain, increases that are likely related to changes in the menstrual cycle. 25 In a population-based postal study performed in Iceland, women with dysmenorrhea were revealed to experience IBS symptoms more frequently than those without dysmenorrhea.…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…Similar to migraine, IBS can alter gut microflora composition and thereby may affect the gut-brain axis and inflammatory status [13,[89][90][91][92][93]. Moreover, food allergies/intolerances that seem to cause migraine attack initiation and relapse of IBS may also explain the association between the disorders [92]. With respect to this, food elimination diets based on IgG antibodies may effectively reduce symptoms in migraine patients with concomitant IBS [94].…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…IBS is well known as intestinal disorder often associated to other functional pain conditions and various extraintestinal co-morbidities [14][15][16] Several pelvic floor conditions are reported by multiple studies as comorbidities associated to IBS: pelvic organ prolapse, urinary urgency, latency or incontinence…”
Section: Resultsmentioning
confidence: 99%